2008
DOI: 10.1021/ja801332d
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Conformational Analysis of Partially Folded Proteins from Residual Dipolar Couplings: Application to the Molecular Recognition Element of Sendai Virus Nucleoprotein

Abstract: A significant fraction of proteins coded in the human proteome do not fold into stable three-dimensional structures but are either partially or completely unfolded. A key feature of this family of proteins is their proposed capacity to undergo a disorder-to-order transition upon interaction with a physiological partner. The mechanisms governing protein folding upon interaction, in particular the extent to which recognition elements are preconfigured prior to formation of molecular complexes, can prove difficul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
157
1

Year Published

2010
2010
2011
2011

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 130 publications
(168 citation statements)
references
References 62 publications
10
157
1
Order By: Relevance
“…In further support of this observation, the many observable and relatively sharp NMR resonances in both NiV and HeV N TAIL -P XD complexes, displaying chemical shifts that are nearly unaltered, provide evidence that N TAIL remains significantly disordered even in the bound form. Therefore the final complex is likely endowed with flexible appendages in a structural arrangement possibly reminiscent of that observed in the case of the MeV complex (44) and also proposed for SeV (84).…”
Section: The X Domains Of Henipavirus P Proteins Bind To the Intrinsimentioning
confidence: 64%
“…In further support of this observation, the many observable and relatively sharp NMR resonances in both NiV and HeV N TAIL -P XD complexes, displaying chemical shifts that are nearly unaltered, provide evidence that N TAIL remains significantly disordered even in the bound form. Therefore the final complex is likely endowed with flexible appendages in a structural arrangement possibly reminiscent of that observed in the case of the MeV complex (44) and also proposed for SeV (84).…”
Section: The X Domains Of Henipavirus P Proteins Bind To the Intrinsimentioning
confidence: 64%
“…55,56 Therefore, a large number of theoretical 55,57 and experimental studies 14,18,[58][59][60][61] of IDPs has focused on identifying elements of partially formed secondary structure, particularly a-helices. In experimental studies trying to identify partially formed helices, it is desirable to work under conditions where the helical elements have the highest population.…”
Section: Discussionmentioning
confidence: 99%
“…The structure of a disordered peptide chain is thus far from random, and we will use the term statistical coil instead of ''random coil'' throughout the remainder of this text. Subsequent studies have shown that some IDPs required a higher proportion of helical-or PPII-like conformations to fit the experimental data, 17,18 which underscores that the free energy landscape for residual structure in IDPs is best evaluated on a case-to-case basis and with residue resolution.…”
Section: Introductionmentioning
confidence: 99%
“…In this study we have developed an atomic resolution ensemble description of isolated N TAIL from MeV using recently developed tools designed to provide quantitative descriptions of conformational equilibria in IDPs on the basis of experimental NMR data (14)(15)(16). Chemical shifts (17,18) and residual dipolar couplings (RDCs) (19,20), measured in a weakly ordering alignment medium were combined to directly probe the level and nature of residual structure in N TAIL , revealing that while the majority of N TAIL behaves like an intrinsically disordered chain, the MoRE exists in a rapidly interconverting conformational equilibrium between an unfolded form and conformers containing one of four discrete α-helical elements situated around the interaction site (Fig. 1, Fig.…”
Section: N Tail Populates a Dynamic Equilibrium Comprising Preencodedmentioning
confidence: 99%
“…All of these α-helices are found to be stabilized by N-capping interactions mediated by side chains of four different aspartic acids or serines that precede the observed helices (21,22). N-capping stabilization of helices or turns represents an important mechanism by which the primary sequence encodes prerecognition states in disordered proteins, and has been observed in the proteins Tau (23), Sendai virus N TAIL (19), the N-terminal transactivation domain of p53 (24), and the ribosomal protein L9 (25).…”
Section: N Tail Populates a Dynamic Equilibrium Comprising Preencodedmentioning
confidence: 99%